Prevalence and Risk Factors of Anemia among Antenatal Mothers Registered at a District Hospital in North India: A Cross-sectional Record Based Study - Rajesh Kumar Kotwal; Rakesh Kotwal; Kiran Bala; Bhavna Sahni (RGUHS Journal of Nursing Sciences)
Background Anemia is the most common disorder which contributes significantly to high maternal mortality. Despite the availability of low-cost effective interventions for prevention and treatment of anemia among pregnant women its prevalence is still high.Objective This study aimed to check the prevalence of anemia and its associated risk factors among pregnant women attending a secondary level health care center in North India.Method A cross-sectional record-based study was carried out at a District Hospital in North India to study the prevalence and risk factors of anemia among the registered antenatal females.Results Mean age of antenatal females was 27.68plusmn4.59 years Range 18 ndash 45 years. Around 89.38 females were fully immunized with tetanus toxoid TT 8.94 had taken only one dose and 1.68 were unimmunized. About 96.08 of pregnant women had taken iron folic acid IFA supplementation. 78.77 delivered normally while one-fifth delivered through lower segment Caesarean section LSCS. 20 of registered females delivered neonates with low birth weight. 97.21 pregnant mothers were found to be anemic. 19.55 59.22 and 18.44 pregnant women had mild moderate and severe anemia respectively. Moderate anemia was highest in second order pregnancies while severe anemia was highest in third order pregnancies. Severe anemia was higher among caesarean deliveries 28.95 in comparison to normal deliveries 15.60. There was statistically significant difference between hemoglobin levels of women who delivered low birth weight and those who delivered normal weight babies p0.017 and also between females who had received TT and those who were unimmunized p0.002.Conclusion Anemia in pregnancy continues to be a major public health challenge. Rigorous efforts for implementation of various maternal health schemes at grass root level are imperative to reduce its catastrophic consequences.